Activities of the political agency of the Russian empire in the emirate of Bukhara - KHOLIKOVA, RAKHBAR ERGASHEVNA (The journal of contemporary issues in business and government, 2021)
We know that in the second half of the 19th century and the beginning of the 20th century, the Tsarist government pursued military action against the Bukhara Emirate not only for political, military and strategic reasons, but also for economic interests. The establishment of the political agency of the Russian Empire in Bukhara on the basis of the order of the Russian tsar in January 1886 subjected him to interference in the internal affairs of Bukhara due to his control over the emirs and ministers of Bukhara even passed into his hands the appointment of officers and officials of the Bukhara state. This shows that the Government of Tsarist Russia and its administrators in the Turkic country gradually entered the economy of the emirate of Bukhara and gained full control over it. In the research work, these same processes are analyzed on the basis of Russian State Archive of Military History sources and literature.